Incremental value of cardiac deformation analysis in acute myocarditis: a cardiovascular magnetic resonance imaging study - André, Florian; Stock, Florian Timothy; Riffel, Johannes; Giannitsis, Evangelos; Steen, Henning; Scharhag, Jürgen; Katus, Hugo; Buß, Sebastian Johannes (The international journal of cardiovascular imaging, 2016)
The aim of this study was to assess cardiac deformation patterns in myocarditis applying feature tracking imaging (FTI) to cardiovascular magnetic resonance (CMR) images. Thirty-six patients (31 males) with acute myocarditis and 36 age- and gender-matched healthy volunteers were studied. CMR examinations were performed in a 1.5 T MR-scanner including late gadolinium enhancement (LGE). FTI was applied to standard cine images of long and short axis views. Global peak circumferential, longitudinal and radial systolic strains as well as long axis strain (LAS) were measured. Patients showed significantly impaired global peak circumferential (−24.4 ± 4.2 % vs. −28.8 ± 3.8 %, p < 0.0001), longitudinal (−17.6 ± 4.4 % vs. −23.8 ± 3.1 %, p < 0.0001) and radial (26.1 ± 5.4 % vs. 37.9 ± 7.6 %, p < 0.0001) systolic strains. Even patients with a preserved ejection fraction (pEF, ≥55 %) had significantly reduced longitudinal (−20.0 ± 4.8 % vs. −23.8 ± 3.1 %, p < 0.01) and radial (27.7 ± 5.5 % vs. 37.9 ± 7.6 %, p < 0.0001) strains. The extent of LGE in patients did not correlate to their respective strains. Regarding the differentiation between patients and controls, the addition of global peak systolic strains to ejection fraction led to a significant improvement of the logistic regression model (χ2 48.7 vs. 71.5; p < 0.001) resulting in a high AUC of 0.98. Applying previously published reference values, 75 % or 31 % of patients with pEF showed at least one strain value or a LAS, which fell below the limit of 1 or respectively 2 standard deviations from the reference mean value. Cardiac strains measured by CMR-FTI are significantly impaired in patients with acute myocarditis even in those with pEF. Therefore, strain assessment may improve the diagnostic accuracy of CMR for myocarditis.